(3QSGdI GHf SjfG Edi CHj GdQjMGf aj LhGH eSGFd CfaPgG Edjg ef NhGQRe hGYJQGV dGHi GdQjMGf Ydi gPG GdLhGHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3MGWc Gddg eZHhWG fHjd eG jghGg hGSJZc dLejY eG JJefGg s
(3BNQgG (B:s
(3hjLH Cf GTcd Ydjc TF ef gPg GdaUhd Cf Jefi Ydi HeYGhOI GdeWGdHI HTQMgG MJi CYLd ai EjVGMgG hEfbGVgG Edjc s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(599) s
Keywords: (3GdadSaI hGdefWbs